PENGARUH PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG NYAMUK AEDES SP TERHADAP PERILAKU PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Purnamasari, A. Bida; Dirawan, Gufran D. (Pascasarjana Universitas Negeri Makassar, 2025)
Dengue Hemorrhagic Fever (DHF) remains one of the major public health problems worldwide and in Indonesia. The World Health Organization (WHO) has reported that the incidence of dengue has increased sharply over the past few decades. WHO has even classified dengue as one of the top ten threats to global health, and Indonesia is one of the countries with the highest incidence. This study aims to determine the extent to which community knowledge and attitudes about Aedes spp. mosquitoes influence DHF prevention behaviors. The study employed an analytic quantitative design with a cross-sectional approach. The sample was selected using simple random sampling from community members living in Makassar City. A total of 75 respondents from several urban villages participated in the study. Data were collected using a questionnaire consisting of two main sections: knowledge (covering facts, concepts, and procedures) related to Aedes mosquitoes and DHF, and attitudes (covering cognitive, affective, and conative components). Data were analyzed using univariate analysis to describe the distribution of knowledge and attitudes. The results showed that most respondents (84%) had knowledge in the very high category regarding Aedes aegypti, followed by 10% in the high category and 6% in the medium category, with no respondents falling into the low or very low categories. This pattern indicates that, in general, respondents’ knowledge of Aedes aegypti is at a very good level. Meanwhile, respondents’ attitudes toward DHF preventive behaviors tended to be highly positive. A total of 25 respondents (33%) were in the very high attitude category and 48 respondents (64%) were in the high category; combined, approximately 97% of respondents demonstrated positive attitudes toward DHF prevention efforts. These findings are consistent with various KAP (knowledge, attitude, practice) studies showing that in communities with adequate exposure to dengue-related information, attitudes toward DHF prevention are generally in the good to very good categories.